2021
DOI: 10.1093/femspd/ftab017
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, drivers and global health implications of the 2019/2020 yellow fever sporadic outbreaks in Sub-Saharan Africa

Abstract: The 2019 and 2020 sporadic outbreaks of Yellow fever (YF) in Sub-Saharan Africa (SSA) countries had raised a lot of global health concerns. This article aims to narratively review the vector biology, YF vaccination program, environmental factors and climatic changes, and to understand how they could facilitate the re-emergence of YF. This study comprehensively reviewed articles that focused on the interplay and complexity of YF Virus (YFV) vector diversity/competence, YF vaccine immunodynamics, and climatic ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…In the human domain, human activities and susceptibility due inadequate acquired immunity contribute to the sustained occurrence of YF [28,29]. For instance, research revealed that changes in land use may influence the shift from sylvatic-to-urban YF transmission cycles [30].…”
Section: One Health Domains and Yf In Ugandamentioning
confidence: 99%
See 2 more Smart Citations
“…In the human domain, human activities and susceptibility due inadequate acquired immunity contribute to the sustained occurrence of YF [28,29]. For instance, research revealed that changes in land use may influence the shift from sylvatic-to-urban YF transmission cycles [30].…”
Section: One Health Domains and Yf In Ugandamentioning
confidence: 99%
“…The environmental factors encompass climate and seasonal temperature variation, changes in urbanization and land use, and vector population distribution. Important environmental and bioclimatic data have demonstrated that prevalence of zoonotic diseases is both sustained and exacerbated by shifts in average temperature, total annual precipitation, and relative humidity [30,34,35]. The rise in precipitation and warmer temperatures likely expanded mosquito populations in affected regions [30].…”
Section: One Health Domains and Yf In Ugandamentioning
confidence: 99%
See 1 more Smart Citation
“…Reoccurring YF cases involving sylvatic cycles have been described in Brazil since 2016 [3][4][5][6]. Furthermore, outbreaks based on urban cycles were reported in Sub-Saharan African countries in 2019 and 2020 [7][8][9]. While YF is absent in the Asia-Pacific region, Dengue occurs in the Asia-Pacific region as well as Africa, the Americas, and the Eastern Mediterranean with Asia representing about 70% of the global burden of disease [10][11][12].…”
Section: Introductionmentioning
confidence: 99%